EFFECTIVENESS OF ORALLY USE CATFISH (Clarias gariepinus) SKIN AND MEAT ON WOUND LENGTH AND FIBROBLAST DENSITY IN INCISION WOUND OF WISTAR RAT (Rattus norvegicus) - Sri Utami Fauziah; Risnandya Primanagara; Tiar M. Pratamawati; Donny Nauphar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Treatment for wounds that are currently often given is use povidone-iodine. But, this antiseptics also kills fibroblast tissue which is useful for forming new tissue. One of the other ways to treatment for wounds is use catfish. The contents found in catfish (Clarias gariepinus) is albumin which is a globular protein that is useful in the formation of body tissues, such as postoperative wounds and burns. This study aims to determine the effect of skin and meat of catfish (Clarias gariepinus) on wound length and fibroblast density in incision wounds of Wistar rat (Rattus norvegicus). Methodology: This study is an experimental study with Post Test Only Control Group Design using Wistar rats which are divided into five groups. The control group (aquadest) and treatment groups 1, 2, 3 and 4 are given the skin and meat of catfish (Clarias gariepinus) orally at a dose of 12.5 mg / 200 g BW, 25 mg / 200 g BW, 37.5 mg / 200 g BW, and 50 mg / 200 g BW. After 10 days, the rats are killed to take the wound tissue for histological preparations to observe fibroblast density. Then, it is analyzed by ANOVA test or the alternative. Results: There is an effect of giving catfish skin and meat (Clarias gariepinus) orally at different dose. The administration of catfish skin and meat (Clarias gariepinus) at a dose of 37.5 mg / 200 g BW and 50 mg / 200 g BW is better than other doses assessed from wound length and fibroblast density in Wistar rat incision wounds (Rattus norvegicus). Conclusion: The use of catfish for wound healing can be applied. This method can reduce wound length and increase fibroblast density at certain doses. Keywords: Fibroblasts, incision wounds, catfish, Clarias gariepinus, wound healing